(3JYdje GdadSaI aj GdGSdGe (B((3ef GdbQf GdKGef GdejdGOj MJi GdbQf GdKGfj YTQ(B)s - (3gRjeI, KfjG UHMjs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2004)
(3jhGLg GdYGde GdYQHj CReI aj JYdje GdadSaI, hjQJHW GdNWGH GdadSaj GdLGeYj aj dHfGf HGdETcGdjI GdYGeI ddSjGSI GdJYdjejI, ajNdh ef efWdbGJg GdacQjI hJWdYGJg GdGLJeGYjI ef GdJhLgGJ GdYGeI hGdeTJQcI hGdTehdjI, hdG jMed JWhQG efSLeG Yf GdEfSGf hGdeLJeY, ddOaGY Yf GdadSaI hJYdjegG, hdJUhjH Gdehba efgG, YGOJ GdOQGSI Edi GdeUGOQ aj GdLPhQ, dJHMK Yf ehbY GdadSaI aj GdacQ GdYQHj GdESdGej, heOi ehGabJgG ddOjf, hdJHMK aj efGgL JYdje GdadSaI, CSGdjH GdJYdje hZGjGJg, hdJDcO Ydi OhQ GdadSaI aj UYhO GdMVGQI GdYQHjI(B. (3JfGhdJ GdOQGSI JYdje GdadSaI aj GdeTQb hGdeZQH GdYQHj ef GdbQf GdKGef GdejdGOj Edi GdbQf GdKGfj YTQ, HOAG HJhVjM GdCUhd GdjhfGfjI dJYdje GdadSaI YfO GdYQH hGdeSdejf, TGQMI CTcGd JYdje GdadSaI, hefGgLgG, hHNGUI YfO SbQGW, CadGWhf, hCQSWh hWQb GdJYdje hCgOGag(B. (3JWQbJ GdOQGSI Edi GdehGVjY GdJGdjI(B: (3CKQ GdSjGSI aj GfHYGK GdadSaI, GdJQHjI GdESdGejI hJYdje GdadSaI, Ege GdeJcdehf aj GdESdGe HGdbVGjG GdadSajI, GdJYdje GdUhaj, JYdje GdadSaI GdSQj, GdadSaI aj GdZQH GdESdGej(B. (3hbO NJeJ GdOQGSI HGdJCcjO Ydi GdOhQ GdcHjQ ddadSaI hJYdjegG aj UYhO GdMVGQI GdYQHjI, aGdeSDhdjI edbGI Ydi GdJQHjI hGdJYdje HOhQ GdJCSjS dJMbjb GdeTQhY GdhWfj GdOjebQGWj, hGdhSjdI dHdhZ gPg GdZGjI gh JYdje GdadSaI GdJj JYfi bHd cd TjA HGdYbd hbhGYOg hfTGWg(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Education Islamique; Islamic Education; L$1 (Benseignement de la Philosophie et la Morales; Philosophy and Moral Education; (3GdJQHjI GdGSdGejIs; (3JYdje GdadSaI hGdGNdGbs